Réponses

2013-05-29T13:50:34+02:00

Bonjour

 

G = (x-5)² - (x-5)(7 - 2x)

G = x² -10x+25 - ( 7x -2x² -35 +10x)

G = x² -10x +25 -7x +2x² +35 -10x

G = 3x² -27 x +60

 

G = (x-5)(x-5) - (7-2x)

G = (x-5)(x-5-7+2x)

G = (x-5)(3x -12)

Pour x = -3

G = (-8)(-9-12) = -8 x -21 = 168

 

(x-5)(3x-12) = 0

soit x-5 = 0 alors x = 5

soit 3x-12 = 0 donc 3x = 12 et x = 4

2013-05-29T13:51:49+02:00

G = (x-5)^2 - (x-5)(7-2x)

G = x^2 - 5^2 - 7x + 2x^2 + 35 + 10x

G = 3x^2 + 3x + 10

 

PS : ^2 est le signe "au carré"